Environmental effects on stellar populations of star clusters and dwarf galaxies. Issue Volume 12:Issue S316(2015) (31st March 2017) - Pasetto, Stefano; Cropper, Mark; Fujita, Yutaka; Chiosi, Cesare; Grebel, Eva K.
Abstract: We investigate the competitive role of the different dissipative phenomena acting on the onset of star formation of gravitationally bound systems in an external environment. Ram pressure, Kelvin-Helmholtz and Rayleigh-Taylor instabilities, and tidal forces are accounted for separately in an analytical framework and compared in their role in influencing the star forming regions. We present an analytical criterion to elucidate the dependence of star formation in a spherical stellar system on its surrounding environment. We consider the different signatures of these phenomena in synthetically realized colour-magnitude diagrams (CMDs) of the orbiting system thus investigating the detectability limits of these different effects for future observational projects and their relevance. The developed theoretical framework has direct applications to the cases of massive star clusters, dwarf galaxies in galaxy clusters and dwarf galaxies orbiting our Milky Way system, as well as any primordial gas-rich cluster of stars orbiting within its host galaxy.